Effects of static and progressively increasing prey density regimens on larval performance of largemouth bass (Micropterus nigricans) reared in an intensive recirculating aquaculture system - Nelson S. Parajuli; Robert Glennon; Anneleen Swanepoel; Dustin Goodman; Josh Sakmar; Allen Nicholls; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Ian A.E. Butts (Aquaculture, 2027)

Acute thermal stress alters sperm swimming activity, viability, and gene expression in blue catfish, Ictalurus furcatus - Kaylan M. Price; Brian G. Bosworth; Samitha S.N. Liyanage; Jason W. Abernathy; Benjamin H. Beck; Luke A. Roy; Timothy J. Bruce; Rex A. Dunham; Ian A.E. Butts (Theriogenology, 2026)

Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

The Effects of Peracetic Acid on Post‐Larvae and Juvenile Pacific White Shrimp ( Litopenaeus vannamei ) and Seven Vibrio Species Isolates at Two Salinities - James T. Tuttle; Timothy J. Bruce; Luke A. Roy; Hisham A. Abdelrahman; Julio C. García; Benjamin H. Beck; David L. Straus; Anita M. Kelly (Journal of Fish Diseases, 2026)
Pacific white shrimp ( Litopenaeus vannamei ) are among the most important aquaculture species but are highly susceptible to Vibrio infections. Novel disease management strategies are necessary. Previous studies have reported that peracetic acid (PAA) is an effective disinfectant, but its application in shrimp aquaculture remains underexplored. This study aimed to determine the median lethal concentration (LC 50 ) of PAA at two life stages of L. vannamei under two salinities and assess its in vitro growth‐inhibitory effects against Vibrio spp. Two groups of 180 juveniles (~5 g) and post‐larvae (maintained at either 4 or 30 g L −1 ) were exposed to six geometrically increasing concentrations of PAA to determine 24‐h LC 50 estimates. Representative juvenile shrimp tissues were histologically assessed. Seven isolates of Vibrio spp. inocula were exposed to PAA and enumerated to determine growth inhibition. The LC 50 estimates varied from 29.09 to 82.40 mg L −1 of PAA. Gill and hepatopancreas tissues were notably damaged at 40.5 and 75 mg L −1 of PAA at 4 and 30 g L −1 , respectively. Growth of all Vibrio spp. was inhibited at the lowest PAA dose tested, that being 0.03125 mg L −1 after 45 min. These findings will help progress the further application of peracetic acid in shrimp aquaculture.

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

Effect of short-term storage on sperm quality and microbiome dynamics in blue catfish, Ictalurus furcatus - Samitha S.N. Liyanage; Kasun A. Bandara; Kaylan A. Martin; Kyle R. Wood; Jason W. Abernathy; Benjamin H. Beck; Timothy J. Bruce; Luke A. Roy; Rex A. Dunham; Xu Wang; Ian A.E. Butts (Aquaculture, 2026)

Cryopreservation techniques for blue catfish, Ictalurus furcatus, sperm using 2.5 mL straws - Kyle R. Wood; Brian Bosworth; Samitha S.N. Liyanage; Alexandra E. Nowicki; Kaylan A. Martin; Rex A. Dunham; Benjamin H. Beck; Jason W. Abernathy; Xu Wang; Luke A. Roy; Ian A.E. Butts (Cryobiology, 2025)

Tissue Mosaicism in Xenogenic Common Carp (Cyprinus carpio) Injected with Unsorted Gonadal Cells from Blue Catfish (Ictalurus furcatus) - Baofeng Su; Logan Bern; Kate B. Pottle; Darshika Udari Hettiarachchi; Mei Shang; Veronica Alston; Jacob Al-Armanazi; Misha Soman; Hamza Dilawar; Jinhai Wang; Ian A.E. Butts; Luke A. Roy; et al. (Marine Biotechnology, 2025)

Parental impacts on industry-relevant offspring performance traits using blue catfish, Ictalurus furcatus (Valenciennes, 1840), cryopreserved sperm - Kyle R. Wood; Ying Zhang; V. MacKenzie Tackett; Kaylan A. Martin; Samitha S.N. Liyanage; Benjamin H. Beck; Jason W. Abernathy; Rex A. Dunham; Luke A. Roy; Xu Wang; Ian A.E. Butts (Theriogenology, 2025)

Resistome and microbiome shifts in catfish rearing water: the influence of temperature and antibiotic treatments - Xiran Li; Hongye Wang; Hisham A. Abdelrahman; Anita M. Kelly; Luke A. Roy; Esteban Soto; Luxin Wang (Water Research, 2025)

Sperm fatty acid composition as an indicator of quality and cryotolerance in blue catfish, Ictalurus furcatus - Kyle R. Wood; Matthew K. Litvak; Samitha S.N. Liyanage; Kaylan A. Martin; V. MacKenzie Tackett; Rex A. Dunham; Luke A. Roy; Cynthia K. Faulk; Benjamin H. Beck; Jason W. Abernathy; Xu Wang; Ian A.E. Butts (Theriogenology, 2025)

“The use of Corn fermented protein as a protein source complement with soybean meal in practical diets in pond and tank based production of Pacific white shrimp (Litopenaeus vannamei).” - Cristhian F. San Andres; Khanh Q. Nguyen; Jairo A. Gonzalez; Arnold J. Gutierrez; Melanie A. Rhodes; Julio García; Luke A. Roy; D. Allen Davis (Animal Feed Science and Technology, 2025)

Influence of dietary fermented yeast products (Saccharomyces cerevisiae) on performance, health and microbiome of Nile tilapia (Oreochromis niloticus) and the influence of discharge water in the production of romaine lettuce (Lactuca sativa) - Uthpala M. Padeniya; D. Allen Davis; Daniel E. Wells; Courtney E. Harrison; Benjamin R. LaFrentz; Benjamin H. Beck; Luke A. Roy; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

The Fertilization of Synbiotic Systems in the Intensive Culture of Penaeus vannamei - Otávio Augusto Lacerda Ferreira Pimentel; Wilson Wasielesky; Luis Otavio Brito; Luke Aaron Roy; Nicholas Romano; Dariano Krummenauer (Reviews in Aquaculture, 2025)
Over the years, the intensification of shrimp Penaeus vannamei production has brought challenges such as disease outbreaks and increases in the nutrient loading of effluents. To be more environmentally friendly as production systems intensified, it became necessary to create systems with a high degree of biosecurity and toward efficiency in water and land use. Thus, microbial‐based systems, such as the biofloc, were pioneered to support industry growth and market demand for shrimp. Currently, a derivation of biofloc has emerged and is gaining ground in the shrimp industry, which is the synbiotic system. Synbiotic systems are microbially based and are characterized by fertilizing the culture water with vegetable bran (prebiotics) that were processed by fermentation and/or microbial respiration by probiotic microorganisms. The fertilization strategy creates conditions similar to a natural environment by supporting microbial loop development, controlling water quality, and suppressing harmful, and pathogenic microorganisms. The synbiotic system is still new and without standard fertilization protocols, which has leads to dissimilar results between laboratory research and commercial farms. Therefore, this review is focused on describing the different fertilization procedures used in the synbiotic system for P. vannamei intensive culture, the importance of each fertilizer component, as well as the processing strategies. Furthermore, in this study, we seek to demonstrate perspectives and recommend future research topics to better understand the advantages and disadvantages of this production system.

Effects of minimum dissolved oxygen setpoints for aeration in semi-intensive pond production of Pacific white shrimp (Litopenaeus vannamei) - Adela N. Araujo; Christian F. San Andres; Khanh Q. Nguyen; Trenton L. Corby; Melanie A. Rhodes; Julio García; Luke A. Roy; D. Allen Davis (Aquaculture, 2025)

Profiling and source tracking of the microbial populations and resistome present in fish products - Xiran Li; Hongye Wang; Hisham Abdelrahman; Anita Kelly; Luke Roy; Luxin Wang (International Journal of Food Microbiology, 2024)

Molecular biomarkers for sperm quality in an economically important fish: Blue catfish, Ictalurus furcatus - Hana N. Hess; Marie E. Strader; Helen R. Montague; Timothy J. Bruce; Gavin L. Aguilar; Sune R. Sørensen; Laura E. Jenkins; Luke A. Roy; Rex A. Dunham; Ian A.E. Butts (Aquaculture, 2024)

On demand feeding and the response of Pacific white shrimp (Litopenaeus vannamei) to varying dietary protein levels in semi-intensive pond production - Leila M. Strebel; Khanh Nguyen; Adela Araujo; Trenton Corby; Melanie Rhodes; Benjamin H. Beck; Luke A. Roy; D. Allen Davis (Aquaculture, 2023)

In vitro fertilization with frozen-thawed blue catfish (Ictalurus furcatus) sperm and implications for gene banking - Helen R. Montague; Hana N. Hess; V. MacKenzie Tackett; Savannah L. Britt; Larry L. Lawson; Gavin L. Aguilar; Laura E. Jenkins; Luke A. Roy; Leigh W. Holland; Rex A. Dunham; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2023)

Penaeus vannamei inland farming: Perspectives and opinions - Otávio Augusto Lacerda Ferreira Pimentel; Luke Aaron Roy; Elizabeth Pereira dos Santos; Valdemir Queiroz de Oliveira; Luis Otavio Brito (Reviews in Aquaculture, 2023)

Intramammary and systemic use of antimicrobials and their association with resistance in generic Escherichia coli recovered from fecal samples from Canadian dairy herds: A cross-sectional study - Mariana Fonseca; Luke C. Heider; Henrik Stryhn; J.Trenton McClure; David Léger; Daniella Rizzo; Landon Warder; Simon Dufour; Jean-Philippe Roy; David F. Kelton; David Renaud; Herman W. Barkema; et al. (Preventive Veterinary Medicine, 2023)

Source separated graywater: Chemistry, unit operations, and criteria towards re-use - Jacob Lalley; Sarah Grace Zetterholm; Scott Waisner; Edith Martinez-Guerra; Max Wamsley; Luke Gurtowski; Roy Wade; Steve Pranger; Chris Griggs (Journal of Water Process Engineering, 2023)

Antimicrobial use and its association with the isolation of and antimicrobial resistance in Campylobacter spp. recovered from fecal samples from Canadian dairy herds: A cross-sectional study - Mariana Fonseca; Luke C. Heider; Henrik Stryhn; J.Trenton McClure; David Léger; Daniella Rizzo; Landon Warder; Simon Dufour; Jean-Philippe Roy; David F. Kelton; David Renaud; Herman W. Barkema; et al. (Preventive Veterinary Medicine, 2023)

Mechanisms underpinning community stability along a latitudinal gradient: Insights from a niche‐based approach - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Change Biology, 2023)
At large scales, the mechanisms underpinning stability in natural communities may vary in importance due to changes in species composition, mean abundance, and species richness. Here we link species characteristics (niche positions) and community characteristics (richness and abundance) to evaluate the importance of stability mechanisms in 156 butterfly communities monitored across three European countries and spanning five bioclimatic regions. We construct niche‐based hierarchical structural Bayesian models to explain first differences in abundance, population stability, and species richness between the countries, and then explore how these factors impact community stability both directly and indirectly (via synchrony and population stability). Species richness was partially explained by the position of a site relative to the niches of the species pool, and species near the centre of their niche had higher average population stability. The differences in mean abundance, population stability, and species richness then influenced how much variation in community stability they explained across the countries. We found, using variance partitioning, that community stability in Finnish communities was most influenced by community abundance, whereas this aspect was unimportant in Spain with species synchrony explaining most variation; the UK was somewhat intermediate with both factors explaining variation. Across all countries, the diversity–stability relationship was indirect with species richness reducing synchrony which increased community stability, with no direct effects of species richness. Our results suggest that in natural communities, biogeographical variation observed in key drivers of stability, such as population abundance and species richness, leads to community stability being limited by different factors and that this can partially be explained due to the niche characteristics of the European butterfly assemblage.

Relationship between aerobic scope and upper thermal limits of Pacific white shrimp (Litopenaeus vannamei) in low-salinity culture systems - Aya S. Hussain; Kaelyn J. Fogelman; Hisham A. Abdelrahman; Luke A. Roy; James A. Stoeckel (Aquaculture, 2023)

Effects of temperature and subspecies during critical early life history stages of largemouth bass (Micropterus salmoides) - Gavin L. Aguilar; Josh Sakmar; Allen Nicholls; Matthew K. Litvak; Hana N. Hess; Timothy J. Bruce; Helen R. Montague; Anita M. Kelly; Luke A. Roy; Moisés A. Bernal; Sebastian N. Politis; Ian A.E. Butts (Aquaculture, 2023)

To seal or not to seal following an antimicrobial infusion at dry-off? A systematic review and multivariate meta-analysis of the incidence and prevalence of intramammary infections post-calving in dairy cows - Mohamed Afifi; Henrik Stryhn; Javier Sanchez; Luke C. Heider; Fidèle Kabera; Jean-Philippe Roy; Sandra Godden; Simon Dufour (Preventive Veterinary Medicine, 2023)

Epidemiology and economic impact of disease-related losses on commercial catfish farms: A seven-year case study from Alabama, USA - Hisham A. Abdelrahman; William G. Hemstreet; Luke A. Roy; Terrill R. Hanson; Benjamin H. Beck; Anita M. Kelly (Aquaculture, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Bioclimatic context of species' populations determines community stability - Luke Christopher Evans; Yolanda Melero; Reto Schmucki; Philipp H. Boersch‐Supan; Lluís Brotons; Colin Fontaine; Frédéric Jiguet; Mikko Kuussaari; Dario Massimino; Robert A. Robinson; David B. Roy; Oliver Schweiger; et al. (Global Ecology and Biogeography, 2022)
Aim It is important to understand the factors affecting community stability because ecosystem function is increasingly at risk from biodiversity loss. Here, we evaluate how a key factor, the position of local environmental conditions within the thermal range of the species, influences the stability of butterfly communities at a continental scale. Location Spain, UK and Finland. Time period 1999–2017. Major taxa studied Butterflies. Methods We tested the following hypotheses about how species responses to temperature anomalies aggregate to influence stability: Hypothesis 1, species have contrasting responses to local temperature anomalies at opposing edges of their thermal range; hypothesis 2, communities with central thermal range positions have higher community stability; and the impacts of thermal range position on community stability are driven by hypothesis 3, population asynchrony, or hypothesis 4, additive population stability. Data were analysed at 876 sites for 157 species. Results We found some support for hypothesis 1, because there were interactions between thermal range and response to temperature anomalies such that species at different range edges could provide weak compensatory dynamics. However, responses were nonlinear, suggesting strong declines with extreme anomalies, particularly at the hot range edge. Hypothesis 2 was supported in part, because community stability increased with central thermal range positions and declined at the edges, after accounting for species richness and community abundance. Thermal range position was weakly correlated with asynchrony (hypothesis 3) and population stability (hypothesis 4), although species richness and population abundance had larger impacts. Main conclusions Future extreme heat events will be likely to impact species negatively across their thermal range, but might be particularly impactful on populations at the hottest end of the thermal range. Thermal range position influenced community stability because range edge communities were stable. However, the prediction of community stability from thermal range position is challenging because of nonlinear responses to temperature, with small temperature anomalies producing weak compensatory dynamics, but large extreme events synchronizing dynamics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Endophytes vs tree pathogens and pests: can they be used as biological control agents to improve tree health? - Mojgan Rabiey; Luke E. Hailey; Shyamali R. Roy; Kristina Grenz; Mahira A. S. Al-Zadjali; Glyn A. Barrett; Robert W. Jackson (European Journal of Plant Pathology, 2019)

Comparative cytogenetic characterization of primary canine melanocytic lesions using array CGH and fluorescence in situ hybridization - Kelsey Poorman; Luke Borst; Scott Moroff; Siddharth Roy; Philippe Labelle; Alison Motsinger-Reif; Matthew Breen (Chromosome Research, 2015)

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Shrimp culture in inland low salinity waters - Luke A. Roy; D. Allen Davis; I. Patrick Saoud; Chris A. Boyd; Harvey J. Pine; Claude E. Boyd (Reviews in Aquaculture, 2010)
Inland aquaculture of shrimp in low salinity waters is widespread in many regions worldwide. Owing to its ability to grow and survive in low salinity environments the Pacific white shrimp, ( Litopenaeus vannamei Boone) has become the candidate of choice for low salinity culture. Remediation techniques have been developed to improve the osmoregulatory capacity of shrimp reared in low salinity waters. These techniques have evaluated water modification strategies that improve low salinity waters used for production by adding potassium and magnesium fertilizers and dietary approaches that involve modification of the feeds offered to shrimp with supplements that might improve osmoregulatory capacity. Based on our own experience as well as what we found predominantly in the literature, it appears that modification of the rearing medium with potassium and magnesium fertilizers is more effective than dietary modification techniques at improving the growth, survival and osmoregulatory capacity of shrimp reared in low salinity waters.